2019
DOI: 10.1101/575209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connectivity profile of thalamic deep brain stimulation to effectively treat essential tremor

Abstract: Essential tremor is the most prevalent movement disorder and is often refractory to medical treatment. Deep brain stimulation offers a therapeutic approach that can efficiently control tremor symptoms. Several deep brain stimulation targets (ventral intermediate nucleus, zona incerta, posterior subthalamic area) have been discussed for tremor treatment. Effective deep brain stimulation therapy for tremor critically involves optimal targeting to modulate the tremor network. This could potentially become more ro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(104 citation statements)
references
References 91 publications
(107 reference statements)
9
95
0
Order By: Relevance
“…This study demonstrates that SID in essential tremor patients is related to a modulation of the functional connectome of speech production by thalamic DBS. In spite of the Running head: Networks in DBS-induced dysarthria proximity of functional and structural connectivity patterns for tremor control, as identified by Al-Fatly et al (2019), and deterioration of speech, as identified in the present study, we were able to derive a fiber-based atlas structure, that could help to avoid SID in essential tremor patients. These findings might contribute to future lead placement and postoperative programming strategies.…”
Section: Word Count Discussion: 1769mentioning
confidence: 61%
See 3 more Smart Citations
“…This study demonstrates that SID in essential tremor patients is related to a modulation of the functional connectome of speech production by thalamic DBS. In spite of the Running head: Networks in DBS-induced dysarthria proximity of functional and structural connectivity patterns for tremor control, as identified by Al-Fatly et al (2019), and deterioration of speech, as identified in the present study, we were able to derive a fiber-based atlas structure, that could help to avoid SID in essential tremor patients. These findings might contribute to future lead placement and postoperative programming strategies.…”
Section: Word Count Discussion: 1769mentioning
confidence: 61%
“…This study demonstrates that SID in essential tremor patients is related to a modulation of the functional connectome of speech production by thalamic DBS. In spite of the Running head: Networks in DBS-induced dysarthria proximity of functional and structural connectivity patterns for tremor control, as identified by Al-Fatly et al (2019), and deterioration of speech, as identified in the present study, we were able to derive a fiber-based atlas structure, that could help to avoid SID in essential tremor patients. These findings might contribute to future lead placement and postoperative programming strategies.Keywords: thalamic deep brain stimulation, speech motor system, intelligibility, dysarthria, volume of tissue activated Abbreviations DBS = deep brain stimulation, DDK = diadochokinesis, SID = stimulation-induced dysarthria, PSA = posterior subthalamic area, STN = subthalamic nucleus, TRS = tremor rating scale, VIM = ventral intermediate nucleus, VTA = volume of tissue activated Running head: Networks in DBS-induced dysarthria…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Two studies have validated the pipeline using electrophysiological recordings 52,53 and others have demonstrated that results are capable of explaining clinical improvements across patients, DBS centers and cohorts 2,3,48,54,55 . Still, residual errors of electrode reconstructions cannot be excluded.…”
Section: Stn-dbsmentioning
confidence: 99%